2015
DOI: 10.1055/s-0034-1380286
|View full text |Cite
|
Sign up to set email alerts
|

Bis(tri-tert-butylphosphine)palladium(0) [Pd(t-Bu3P)2]

Abstract: from 2008 to 2011. Currently, she is working towards her Ph. D. at the Otto-Diels-Institute for Organic Chemistry under supervision of Prof. Dr. Anne Staubitz. Her research focuses on transition-metal-catalyzed cross-coupling reactions and semiconducting polymers with alternating heterocycle units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…It was rationalized that by mixing Pd­(dba) 2 (2 mol %) with tri- tert -butylphosphonium tetrafluoroborate [TTBP·HBF 4 ] (4 mol %), the very active bis­(tri- tert -butylphosphine)­palladium­(0) [Pd­( t -Bu 3 P) 2 ] would be formed in situ. The t- Bu 3 P is a strong electron-rich phosphine ligand that proficiently stabilizes the palladium­(II) salt obtained from the oxidative addition step . On the other hand, the bulkiness of the t -Bu 3 P favors the reductive elimination step.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was rationalized that by mixing Pd­(dba) 2 (2 mol %) with tri- tert -butylphosphonium tetrafluoroborate [TTBP·HBF 4 ] (4 mol %), the very active bis­(tri- tert -butylphosphine)­palladium­(0) [Pd­( t -Bu 3 P) 2 ] would be formed in situ. The t- Bu 3 P is a strong electron-rich phosphine ligand that proficiently stabilizes the palladium­(II) salt obtained from the oxidative addition step . On the other hand, the bulkiness of the t -Bu 3 P favors the reductive elimination step.…”
Section: Resultsmentioning
confidence: 99%
“…The t-Bu3P is a strong electron-rich phosphine ligand that stabilise proficiently the palladium(II) salt obtained from the oxidative addition step. 49 On the other hand, the bulkiness of the t-Bu3P favours the reductive elimination step. Thus, when using Pd(dba)2 (2 mol%), TTBP•HBF4 (4 mol%), Cy2NMe (1.5 equiv), TBAC (10 mol%) in DMAc at 80 °C, the 3H-naphtho [2,1-b]pyran 49 was isolated directly in a much improved yield (50%) (Scheme 9; Entry 4, Table 1).…”
Section: Synthesis Of 3-pyridyl-3h-naphtho[21-b]pyrans (Strategy B)mentioning
confidence: 99%
“…48 We hypothesised that this sterically controlled change in ligation state of the reactive intermediate could be the reason for the observed discrepancy. To experimentally confirm that the speciation change also occurs with benzyl electrophiles, we reacted Pd(P t Bu3)2 with excess BnBr and characterised the product of the reaction by 31 P{ 1 H} NMR and single crystal X-ray diffraction, confirming the presence of only one phosphine (Fig. 3b; see SI sections S2.2 and S6).…”
Section: Resultsmentioning
confidence: 97%
“…As a result of several trials, we found that the addition of Hunig’s base kept the reaction solution basic, preventing undesired destannylation of 4 . In addition, the highly active Pd catalyst, Pd­( t -Bu 3 P) 2 , enabled us to carry out the reaction at room temperature, inhibiting undesired side reactions. Finally, the one-pot Stille coupling gave (4 S ,5 R )- 1 , and its 1 H NMR matched that of natural 1 .…”
mentioning
confidence: 99%